The effectiveness of combined preventive treatment with Ceftiofur, Oxytocin and PGF(2 alpha) on fertility parameters in cows - Kaya, D.; Ay, S. S.; Kucukaslan, I.; Beceriklisoy, H. B.; Agaoglu, A. R.; Findik, M.; Aslan, Selcuk (Ecole Nationale Veterinaire Toulouse, 2012)
The present study is aimed at evaluating the effectiveness of combined preventive treatment with Ceftiofur Hydrochloride (CHR), Oxytocin (OXT) and PGF(2 alpha) on fertility parameters and puerperal disorder rates in postpartum (pp) dairy cows. A total of 191 Holstein-Friesian cows were divided into four groups. The cows in group I (GI; n=37) and II (GII; n=69) were treated on a daily basis with CHR and OXT for five and three days pp, respectively. Group III (GIII; n=52) was designed as the PGF(2 alpha) group, and group IV (GIV; n=33) served as a control group. The animals in GI, GII, and Gill were given a PGF(2 alpha) analogue on days 15 and 26 pp. Each group was further divided into subgroups of normal parturition (np) and dystocia (d) when the study results were evaluated. It was found that the first service pregnancy rates for the subgroup of dystocia were significantly higher (P<0.05 and P<0.01) in subgroup GII (76.9%) than in GI (30.0%) and GIV (37.5%). Furthermore, the median time to first service and the median time to pregnancy were longer for cows in subgroup GIVd as compared with subgroups GId, GIId, and GIIId (P<0.001; P<0.01). Group II was found to have the lowest endometritis rates after treatment of subgroups-d and -np. No statistically significant difference was found between the groups with regard to cystic ovary rates after treatment (P>0.05). As the treatment with CHR-OXT combined with PGF(2 alpha) on days 15 and 26 was associated to improved uterine involution patterns and reproductive performance, our results suggest that administration of this preventive treatment would be useful, especially for cases of dystocia.
FINDIK, Murat/0000-0003-1408-2548; Kucukaslan, Ibrahim/0000-0002-3458-4409
WOS: 000311653600008
Keywords: Postpartum cows; preventive treatment; fertility